Clinical Features and Management of a Median Cleft Lip - Koh, Kyung S.; Kim, Do Yeon; Oh, Tae Suk (Archives of Plastic Surgery, 2016)
Background Median cleft lip is a rare anomaly consisting of a midline vertical cleft through the upper lip. It can also involve the premaxillary bone, the nasal septum, and the central nervous system. In our current report, we present the clinical features of 6 patients with a median cleft lip and their surgical management according to the accompanying anomalies.Methods From December 2010 to January 2014, 6 patients with a median cleft lip were reviewed. Five of these cases underwent surgical correction; alveolar bone grafting was performed in a patient with a median alveolar cleft. The surgical technique included inverted-U excision of the upper lip and repair of the orbicularis oris muscle. The mean follow-up period was 20.4 months (range, 7.4–44.0 months).Results The study patients presented various anomalous features. Five patients received surgical correction, 4 with repair of the median cleft lip, and one with iliac bone grafting for median alveolar cleft. A patient with basal sphenoethmoidal meningocele was managed with transoral endoscopic surgery for repair of the meningocele. Successful surgical repair was achieved in all cases with no postoperative complications.Conclusions Relatively mild forms of median cleft lip can be corrected with inverted-U excision with good aesthetic outcomes. In addition, there is a broad spectrum of clinical features and various anomalies, such as nasal deformity, alveolar cleft, and short upper frenulum, which require close evaluation. The timing of the operation should be decided considering the presence of other anomalies that can threaten patient survival.
Keywords: Frontonasal dysplasia; Median facial cleft syndrome; Median cleft lip